Peran Musabaqah Qira'atil Kutub Terhadap Pembelajaran Bahasa Arab di Pondok Pesantren - Halimah, Novita; Nurmala, Mia; Sauri, Sofyan (Attractive : Innovative Education Journal, 2024)
The Nurul Falah Islamic Boarding School has a program that runs from year to year which focuses on improving the knowledge of Arabic language and fiqh which is packaged in the Musabaqoh Qira'atil Polar (MQK). Arabic linguistics in Musabaqah Qira'atil Polar (MQK) is studied using the yellow book, this is because Islamic boarding schools use the yellow book as their teaching material. Therefore, this research aims to observe the role of Musabaqah Qira'atil Polar (MQK) especially in learning Arabic in terms of maharah kalam (speaking skills), maharah Qira'ah (reading skills), and Qawa'id wa tarjamah ( grammar and translation). The research uses qualitative methods with a case study approach, data obtained from interviews, observation and documentation. Then the data was analyzed by triangulation, with stages of data collection (interviews, observation and documentation), data reduction, data presentation, and finally verification. From the results of the research findings, it can be concluded that the MQK carried out in Islamic boarding schools plays a very important role in learning Arabic language knowledge, this is obtained from the preparation process, implementation, and afterwards. Keywords: Arabic Language Learning, Musabaqah Qira’atil Kutub